Level, distribution and long-term development of market power in Finland - Olli-Matti Laine (Bank of Finland, 2018)
This study examines the level, distribution and development of market power in Finland between 1975 and 2016. The paper applies the methods proposed by Hall (2018a) and Hall (2018b). In contrast to some other international evidence, the aggregate level of market power has not risen in Finland during the last decades. The estimate of country level markup ratio in Finland is 1,25. The paper also analyses the distribution of markup ratios across industries. About 90 per cent of industry level markup ratios are between 1 and 1,5. The results suggest that markups are typically higher in exporter firms than in non-exporter firms.
URN:NBN:fi:bof-201809062009
Keywords: D22; D24; F14; L1; 330; market power